MONITORING APPLICATION FOR SUBMISSION OF PBJ TRANSACTION REPORTS ON PPATK - Hadi Iswanto; Verdi Yasin; Johan Johan; Rumadi Hartawan (Journal of Information System, Informatics and Computing, 2023)
Transaction report monitoring is monitoring activities on transaction reports submitted by Goods and/or Other Services Providers to the Financial Transaction Reports and Analysis Center. However, the transaction report monitoring process is still being carried out using Microsoft Excel so that the monitoring process does not run effectively and efficiently. From these problems an idea emerged to create a web-based transaction report monitoring application that can process transaction report data so that the monitoring process is easy for Reporting Analysts to carry out. The methodology used in making this application is the Waterfall method. The programming language used is PHP using the CodeIgniter framework. To display the application using Bootstrap. The database uses MySQL, the standalone server used is XAMPP and the text editor used is Visual Studio Code. If this application is implemented directly in the organization, it can be a solution in increasing the effectiveness and efficiency of the process of monitoring transaction reports.